1981
DOI: 10.1001/archpedi.1981.02130290032012
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With Salicylate Therapy in Adolescents With Juvenile Rheumatoid Arthritis

Abstract: \s=b\ We compared adolescents' compliance with medical regimens with that of younger children and identified characteristics of noncompliant adolescents. Compliance among 82 patients with juvenile rheumatoid arthritis (JRA) was monitored using serum salicylate levels. Fifty-five percent of adolescents and 55% of children were found to have good compliance. Among adolescent patients with JRA, however, the following factors were associated with salicylate therapy noncompliance: longer duration of disease (more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…Rapoff et al reported that half (48%) of 48 American patients with JIA were non-adherent to NSAID treatment [5]. Similarly, Litt and Cuskey found that 45% of 82 patients with JIA were non-adherent to salicylate therapy [12]. In another report, Degotardi et al found 30% non-adherence to medications in patients with JIA [3].…”
Section: Discussionmentioning
confidence: 99%
“…Rapoff et al reported that half (48%) of 48 American patients with JIA were non-adherent to NSAID treatment [5]. Similarly, Litt and Cuskey found that 45% of 82 patients with JIA were non-adherent to salicylate therapy [12]. In another report, Degotardi et al found 30% non-adherence to medications in patients with JIA [3].…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies by Litt and colleagues found that 55% of children and adolescents with JRA were adherent to salicylate medications as determined by serum assays (3,4). In 3 separate within-subject design studies involving 5 patients with JRA (ages 3 to 14 years), baseline adherence with medications was assessed by parental observations or pill counts and ranged from 38 -59% (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined predictors of adherence to medication regimens for JRA. Litt and Cuskey (3) found that lower adherence to salicylate medications among 38 adolescents with JRA was associated with younger age at disease onset, longer disease duration, shorter duration of subspecialty care, greater delay between disease onset and first subspecialty clinic visit, and fewer clinic visits. Litt et al (4) found that higher selfesteem and autonomy (assuming more responsibility for health care in the context of a positive relationship with parents) were predictive of higher adherence to salicylate medications among a separate group of 38 adolescents with JRA.…”
Section: Introductionmentioning
confidence: 99%
“…Mean levels of adherence for patients with gout were 65%, osteoarthritis 53.9% and ankylosing spondylitis 51.4%. Scrutiny of the data demonstrated that only two studies used objective measures of assessment; levels of uric acid (Hernandez et al, 1978) and salicylate (Litt and Cuskey, 1981). The former produced the lowest level of adherence, 32%, and the latter the second lowest (55%).…”
Section: The Magnitude Of Non-adherence In the Rheumatic Diseasesmentioning
confidence: 99%